Biofuels: An alternative to conventional fuel and energy source. (2022) - Priya,; Deora, Prayagraj Singh; Verma, Yash; Muhal, Ram Avtar; Goswami, Chandramani; Singh, Tej
Abstract: This paper gives a complete idea on the biofuel and its generation. In this fast-growing society there is a need of energies for survive. Biofuel, is the process where fossil fuel is replaced by organic material. It is an alternative source which can be also replaced the petroleum-based fuel. It is also the type of sustainable fuel derived from abundant biological sources called biomass. Biomass include a vast range of waste and plants. The objective of this paper is complete study of biofuel and its generation and find out the solution of other energy sources. The conclusion of this paper is that, algae is one of the greatest sources of energy and it can produce a lot of energy and can be replaced the fossil fuel. Biofuel and biomass are the only renewable sources which can replace the fossil fuel directly for the present and future energy restriction, because it is eco-friendly and renewable energy. The key finding of this review is biofuel can be the best substitute of fossil fuels.